Drinfeld Twist and Symmetric Bethe Vectors of Open XYZ Chain with Non-Diagonal Boundary Terms - 陈曦 冯俊 郝昆 吴可 杨文力 杨战营 张耀中 (Communications in theoretical physics, 2012)
With the help of the Drinfeld twist or factorizing F-matrix for the eight-vertex solid-on-solid （SOS） model, we find that in the F-basis provided by the twist the two sets of pseudo-particle creation operators simultaneously take completely symmetric and polarization free form. This allows us to obtain the explicit and completely symmetric expressions of the two sets of Bethe states of the model.